2018
DOI: 10.1111/ecc.12957
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cancer and management in elderly nursing home residents. A descriptive study in 45 French nursing homes

Abstract: This study aimed to determine cancer prevalence occurring after the age of 75 in 45 French nursing homes (NH), as well as residents’ characteristics and parameters associated with cancer‐specific management. Descriptive retrospective study including 214 residents (mean age, 89.7 years) with cancer diagnosed after age 75. The studied parameters were sociodemographic, functional, nutritional and cognitive data; comorbidity assessment; date of tumoral diagnosis; cancer type; tumoral stage; treatment plan; multidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
1
6
1
Order By: Relevance
“…In agreement with several other studies that report frequent omission of standard care in elderly cancer patients (Blakely, Comissiong, Vezeridis, & Miner, ; Guevara et al, ; Liuu et al, ; Livingstone et al, ; Murtha et al, ), we found that those aged ≥70 years were less likely to undergo SLNB. Performing SLNB in the head and neck region can be technically demanding and has been associated with higher false‐negative rates (Tanis, Nieweg, Brekel, & Balm, ).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with several other studies that report frequent omission of standard care in elderly cancer patients (Blakely, Comissiong, Vezeridis, & Miner, ; Guevara et al, ; Liuu et al, ; Livingstone et al, ; Murtha et al, ), we found that those aged ≥70 years were less likely to undergo SLNB. Performing SLNB in the head and neck region can be technically demanding and has been associated with higher false‐negative rates (Tanis, Nieweg, Brekel, & Balm, ).…”
Section: Discussionsupporting
confidence: 93%
“…This category includes a total of 12 studies distributed in four subcategories: patient profiles, cancer management in nursing homes, oncological treatment outcomes, and shared medical decisions [ 17 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies explored the particularities of nursing home residents with cancer and the risk factors for long-term care use [ 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations